Impact of infrared radiation on UVB-induced skin tumourigenesis in wild type C57BL/6 mice. Issue 1 (24th October 2018) - Kimeswenger, Susanne; Sterniczky, Barbara; Kramer, Anne; Tillmann, Katharina; Gamper, Jutta; Foedinger, Dagmar; Petzelbauer, Peter; Jantschitsch, Christian
Abstract : Additional exposure to infrared radiation leads to a more aggressive phenotype of UVB-induced skin tumours in wild type mice. Abstract : Although infrared radiation (IR) represents more than 50% of the solar radiation reaching the Earth's surface, this waveband has been hardly investigated in terms of tumourigenesis. The objective of the present study was to investigate the influence of IR on ultraviolet B (UVB)-induced carcinogenesis in male and female wild type mice. For this purpose, male and female C57BL/6N mice were subjected to a long-term irradiation protocol. Mice were irradiated once neonatally and from the age of eight weeks for 36 weeks with a cumulative dose of 576 kJ m −2 UVB and/or 78 895 kJ m −2 IR. In order to resemble natural sun irradiation, exposure to physiological doses of UVB and IR was performed simultaneously. Mice were screened for arising lesions twice a week. Lesions were excised and histologically diagnosed. Kaplan–Meier analyses were carried out and lesion counts and cumulated hazard rates for the development of lesions in the UVB and IR + UVB-exposed groups in male and female mice were compared. We found that IR-exposure did not change the number of epithelial malignant tumours in UVB-exposed wild type mice. In combination with IR there was a tendency of more tumours with increased malignancy: 23 vs. seven spindle cell shaped sarcomas and seven vs. two MelanA+/S100+ tumours in groups of 35 C57BL/6 mice. IR did not influence UVB-induced carcinogenesis differently in male and female mice. However, comparing UVB and sham irradiated animals irrespective of IR exposure, UVB-induced non-epithelial tumours arose significantly earlier in male mice than in female mice.